Manifesting America the imperial construction of U.S. national space - Rifkin, Mark, 1974- (New York ; Oxford : Oxford University Press, 2009)
In this work, Mark Rifkin explores how writings by Native Americans and former Mexicans challenge the legal narratives that normalize their absorption into US national space.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States -- Territorial expansion; United States -- Territorial expansion -- Historiography; United States -- Boundaries; United States -- Race relations; Indians of North America -- Land tenure; Human territoriality -- Political aspects -- United States -- History; Nationalism -- United States -- History; American literature -- 1783-1850 -- History and criticism; American literature -- 19th century -- History and criticism